KAJIAN PENYEBAB KETERLAMBATAN PELAKSANAAN PROYEK KONSTUKSI GEDUNG DI KOTA KUPANG - Messah, Yunita Afliana; Widodo, Theodorus; Adoe, Marisya L. (Jurnal Teknik Sipil, 2013)
Construction projects are the activities which executed within limited schedule, limited resources to achieve the physical of buildings and other infrastructures. Construction projects entangle contractors, designers consultants , supervisor consultants which each other tied together in work agreements so called contacts . The success of a construction project depends on the fulfilling of the schedule, cost and quality prescribed on the contracts. During the project execution, it is frequently happen that the project takes more time to finished because of parts involved. Therefore, this research is done as a mean to know the factors that cause the delay of construction projects according to contractors, owners, and supervisor consultants. The research is done by propagating questionnaires to contractors, owners, and supervisor consultants. The result obtained should be analysed using mean and variant analysis. The result are: for the contractors, the main factors of delaying is the lock of man power while for the owners and the supervisor consultants, it is the materials supply factors.